2022
DOI: 10.1128/mra.00652-22
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Micrococcus yunnanensis TT9, Isolated from a Healthy Volunteer

Abstract: Micrococcus yunnanensis TT9 was isolated from the forehead of human skin. This strain can grow on Triton X-100. We report the complete whole-genome sequence of this strain, which has one chromosome of 2,470,932 bp (73.0% G+C content) with 2,151 coding sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…[2,3] Recently, Lee et al reported the complete genome sequence of M. yunnanensis TT9 obtained from the skin of the forehead of a healthy volunteer. [4] M. yunnanensis has been characterized as a nonpathogenic organism that shows no external signs of infection in its host. Most studies have focused on the role of M. yunnanensis in industrial wastewater treatment and plant growth promoting activities, [5][6][7] little is known about its role in the medical field.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Recently, Lee et al reported the complete genome sequence of M. yunnanensis TT9 obtained from the skin of the forehead of a healthy volunteer. [4] M. yunnanensis has been characterized as a nonpathogenic organism that shows no external signs of infection in its host. Most studies have focused on the role of M. yunnanensis in industrial wastewater treatment and plant growth promoting activities, [5][6][7] little is known about its role in the medical field.…”
Section: Introductionmentioning
confidence: 99%